The Oxford companion to film - Bawden, Liz-Anne (Oxford University Press, 1976)
World-wide in scope and covering all aspects of film from "AA" certificate and Bud Abbott to Zoom, Zorro and Andre Zvoboda the Companion ranges from silent movies and the beginnings of film to the mid 1970's and includes a wide array of information.